A national survey of the management of implantable cardioverter defibrillators in specialist palliative care settings. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Beattie, James; Butler, Jane; MacCallum, Annie; Fuller, Alice; Johnson, Miriam
Abstract : Background: Implantable cardioverter defibrillators (ICDs), used alone, or sometimes combined with pacemaker-based cardiac resynchronisation therapy, are increasingly inserted to treat those with heart failure (HF) at risk of lethal arrhythmias. Device activity may discomfort dying patients and induce dilemmas for recipients, families and professional carers at the end of life. Methods: Over a 4 week period between February and March 2011, we undertook a web based retrospective survey of ICD management over the preceding 12 months by specialist palliative care (SPC) services across England, Wales and Northern Ireland. Results: Of 95 respondents, 65% were hospice based, 13% were from SPC units in acute trusts, and 22% were from SPC teams working in a variety of care settings without SPC beds. Of the clinical cohort cared for by these SPC professionals, 5.5% were said to have HF either as a primary or secondary diagnosis. 93% of these services accepted patients with ICDs and 55% had treated such individuals over the relevant period. Half used explicit device-related admission documentation but only 26% had a site specific or regional deactivation policy in place. 42 patients were estimated to have required defibrillator deactivation and in >75% of cases, this required the patient to attend an external device clinic or be visited by a member of the cardiology team or industry representative. Importantly, 44% of SPC teams had no access to a magnet for emergency ICD deactivation and only 32% provided staff training in this intervention. Conclusion: The results of this national survey demonstrate inconsistency in ICD management by SPC teams, with gaps in service which may adversely affect end of life care. SPC units need to develop robust policies to document and manage ICDs prospectively, with staff education and ready access to the necessary expertise and equipment.